Memorization as a strategy in music interpretation for pianists - Tyrenius, Eva Kristina (2024)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Artes, Departamento de Música, Programa de Pós-Graduação Música em Contexto, 2024.